Frequency of Metabolic Syndrome in Male Patients with Acute Myocardial Infarction - Khan, MMR; Sana, NK; Basak, PM; Sarker, BC; Islam, M Akhtarul; Jahan, KI; Rashid, MHO; Rahman, MK; Sarker, A; Das, CK; et al. (TAJ: Journal of Teachers Association, 2018)
Background: Acute myocardial infarction is the most common form of coronary heart disease and the single most important cause of premature death worldwide. A large proportion of patients with coronary disease have metabolic syndrome, although the frequency and association of its different components are not well understood. The risk of the metabolic syndrome on AMI has not been well evaluated. Objective: The aim of this study was to assess the prevalence of the metabolic syndrome and its association with AMI patients. This study will help in awareness building in reducing AMI by early detection of metabolic syndrome. Patients and methods: This was a prospective observational study consisted of 222 persons of male AMI patients who were aged >20 years. Patients with first time AMI arriving in CCU of Rajshahi medical college during the period of 2012-2014, were included. Data were collected through interview, clinical examination, and laboratory tests. Five components of metabolic syndrome were defined according to criteria set by modified NCEP ATP III (according to ethnic variation) which had abdominal obesity (waist circumference), FBS, HDL-C, Triglyceride, and hypertension were measured within 24 hrs of AMI. Results: A total of 222 patients diagnosed with AMI were inducted in the study. The mean±SD age of the male was 53.51±11.63 years. Among the male patients highest percentage was in the age group 51-60 years (31.1%) followed by 41-50 years (27%) and then age group >60 (24.3%). Study showed that acute Myocardial infarction patients was more in age group >40 years of age. Highest percentage was observed in abdominal obesity (52.3%) followed by high blood pressure (50.0%) and FPG (46.4%). The Metabolic syndrome was 37.4 % (n=83). Conclusion: The metabolic syndrome was associated with an increased risk of AMI. The metabolic syndrome had a high prevalence in patients with AMI. TAJ 2014; 27(1): 57-61